2014
DOI: 10.1021/jp509020x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Peptide Nanostructures onto an Electrode Surface for Nonenzymatic Oxygen Sensing

Abstract: We report here the fabrication of a biomimetic sensor for direct oxygen reduction; the sensor consists of multicopper oxidases derived from cyclic-tetrameric copper(II) species containing the ligand (4-imidazolyl)ethylene-2-amino-1-ethylpyridine (apyhist) that are self-assembled with L-diphenylalanine micro/nanostructures (FF-MNTs). The [Cu 4 (apyhist) 4 ] 4+ /FF-MNT complex was immobilized onto the surface of a glassy carbon (GC) electrode by poly ion complex formation with a Nafion film. This hybrid membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
19
0
2
Order By: Relevance
“…In a recent electrochemical biosensor, peptide micro/nanostructures are self-assembled with a complex of copper that acts as the oxygen reduction catalyst, immobilized onto a glassy carbon. This biosensor showed a lower detection limit of 0.1 mg l −1 [35]. Most recent optical biosensors based on FRET transducing include a BOD biosensor chip and a ratiometric FRET sensor.…”
Section: Fret Applied To Environmental Biosensingmentioning
confidence: 97%
“…In a recent electrochemical biosensor, peptide micro/nanostructures are self-assembled with a complex of copper that acts as the oxygen reduction catalyst, immobilized onto a glassy carbon. This biosensor showed a lower detection limit of 0.1 mg l −1 [35]. Most recent optical biosensors based on FRET transducing include a BOD biosensor chip and a ratiometric FRET sensor.…”
Section: Fret Applied To Environmental Biosensingmentioning
confidence: 97%
“…Gewirth et al recently reported that several Cu(II)-complexes adsorbed on a carbon black electrode can catalyze the electrocatalytic electron reduction of O2 [10]. Sousa et al evaluated the electrochemical response and the stability of a [Cu4(apyhist)4] 4+ complex (apyhist = 2-(1H-imidazol-4-yl)-N-(1-(pyridin-2-yl)ethylidene)ethanamine) for the fabrication of a novel biomimetic oxygen sensor [11].…”
Section: Introductionmentioning
confidence: 99%
“…The system architecture, modular packaging, and interface electronics of the designed and fabricated is here presented and its characteristics are compared with that of a commercial one for real time monitoring of DO in water. 4 ] 4+ complex (apyhist = 2-(1H-imidazol-4-yl)-N-(1-(pyridin-2-yl)ethylidene)ethanamine) for the fabrication of a novel biomimetic oxygen sensor [11].…”
Section: Introductionmentioning
confidence: 99%
“…A platina (Pt) e outros metais nobres têm sido extensivamente empregados como catalisadores de 4e-na ORR, mas o custo elevado, a escassez e propensão de envenenamento pelo monóxido de carbono, que limita sua vasta aplicação, têm justificado a procura por materiais alternativos eletrocatalíticos. Neste contexto, após a publicação de trabalhos sobre as propriedades de ftalocianinas e porfirinas de cobalto [51], vários outros mediadores moleculares tais como o DNA [52], antraquinona [53,54], azul de polimetileno [55], peptídeos nanoestructurados [56], complexos de cobalto [21,57,58,59,60], ftalocianina tetrassulfonada de ferro (II) e tetra (N-metil-piridil) porfirina de ferro (II) [7], ftalocianina de magnésio (II) [61], níquel Salen [27], vitamina B-12 [62], ABTS-lacase [63], ZnO dopado com RuO2 [64], diamino-o-benzoquinona [65], índigo tetrassulfonato [66]…”
Section: Sensores Eletroquímicos Para a Detecção De Oxigênio E Despreunclassified
“…e eugenol[67] têm sido estudados.A medição contínua da concentração de oxigênio é essencial em muitos procedimentos médicos e aplicações, processos tecnológicos e de monitoramento e análise ambiental. Vários sensores eletroquímicos à base de mediadores ORR têm sido propostos para a determinação de oxigênio dissolvido em água[41,56,57,64,68,69,70,71,72], mas nenhum deles apresenta robustez adequada, requisito importante para competir com eletrodos de Clark. A título de exemplo, naTabela 1apresentam-se distintos sensores eletroquímicos com informações sobre faixa linear, limite de detecção, método eletroquímico empregado e potencial no qual são feitas as determinações analíticas de O2.…”
unclassified